العيوب في الأفلام الرقيقة من النوع ZnO المنماة بطريقة الترسيب الذري الطبقي - متوج نبيل (Latakia University Journal -Engineering Sciences Series, 2016)
In the present paper, we discuss the influence of point defects on electrical and optical characteristics of ZnO thin films grown by the atomic layer deposition (ALD) method on glass and silicon substrates at low temperature (100°C). Room temperature photoluminescence (RT PL) spectra, secondary ion mass spectroscopy (SIMS), and Hall Effect measurements were made for as-grown ZnO layers. The annealing process was performed in air as well as in N2 atmosphere at 400°C for half an hour. The long annealing resulted in a larger reduction in electron concentration. Simultaneously, an evident increase in carrier’s mobility was observed, which may suggest that annealing resulted in a decreased number of native defects in the ZnO layers. Also, it was observed that hydrogen atoms in ZnO samples did not dominate their electrical properties with the increase of electrons concentration نناقش في هذا البحث، تأثير العيوب النقطية على الخصائص الكهربائية والضوئية لأفلام رقيقة من أكسيد الزنك تم تنميتها بطريقة الترسيب الذري الطبقي على ركائز من الزجاج والسيلكون عند درجة حرارة منخفضة (100°C). أنجزت قياسات أطياف التألق الضوئي عند درجة حرارة الغرفة، والأطياف الكتلوية الأيونية الثانوية، وقياسات مفعول هول لطبقات من أكسيد الزنك. أجريت عملية التسخين عند درجة حرارة400 °C لعينة ZnO المنماة على ركيزة من الزجاج في الهواء وفي جو من الأزوت N2 لمدة نصف ساعة. إن التسخين الطويل يؤدي إلى اختزال كبير لتركيز الإلكترونات، وفي نفس الوقت، نلاحظ زيادة واضحة في حركية حاملات الشحنة، الذي قد يؤدي إلى انخفاض عدد العيوب الأصلية في طبقات أكسيد الزنك. لوحظ أيضا أن ذرات الهيدروجين في عينات أكسيد الزنك لا تسيطر على الخصائص الكهربائية بازدياد تركيز الإلكترونات.